Late effects of cancer treatment: consequences for long-term brain cancer survivors. Issue 1 (16th July 2020) - Alemany, Montse; Velasco, Roser; Simó, Marta; Bruna, Jordi
Abstract: Late adverse effects of cancer treatments represent a significant source of morbidity and also financial hardship among brain tumor patients. These effects can be produced by direct neurologic damage of the tumor and its removal, and/or by complementary treatments such as chemotherapy and radiotherapy, either alone or combined. Notably, young adults are the critical population that faces major consequences because the early onset of the disease may affect their development and socioeconomic status. The spectrum of these late adverse effects is large and involves multiple domains. In this review we classify the main long-term adverse effects into 4 sections: CNS complications, peripheral nervous system complications, secondary neoplasms, and Economic impact. In addition, CNS main complications are divided into nonfocal and focal symptoms. Owing to all the secondary effects mentioned, it is essential for physicians to have a high level of clinical suspicion to prevent and provide early intervention to minimize their impact.